2007
DOI: 10.1007/s10620-006-9312-0
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide/Midodrine Therapy Significantly Improves Renal Function and 30-Day Survival in Patients with Type 1 Hepatorenal Syndrome

Abstract: Type 1 hepatorenal syndrome (HRS) can be a rapidly fatal consequence of liver failure. Recent studies have utilized vasoconstrictor therapies to combat splanchnic vasodilatation. We aimed to evaluate the efficacy of a promising treatment for type 1 HRS. We compared the survival of HRS patients who received octreotide and midodrine treatment at Rancho Los Amigos Medical Center with a concurrent untreated control group of HRS patients who did not receive this treatment. Of the 81 patients, 60 were treated with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(79 citation statements)
references
References 25 publications
3
72
0
4
Order By: Relevance
“…Data suggests that the combination of Midodrine, a selective α-1 adrenergic agonist and systemic vasoconstrictor, and Octreotide, a somatostatin analog and inhibitor of endogenous vasodialators, to be effective in prolonging survival in HRS [4,5]. One study using Octreotide alone did prove to be effective in the treatment of HRS [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data suggests that the combination of Midodrine, a selective α-1 adrenergic agonist and systemic vasoconstrictor, and Octreotide, a somatostatin analog and inhibitor of endogenous vasodialators, to be effective in prolonging survival in HRS [4,5]. One study using Octreotide alone did prove to be effective in the treatment of HRS [6].…”
Section: Discussionmentioning
confidence: 99%
“…One study using Octreotide alone did prove to be effective in the treatment of HRS [6]. Results of these studies are summarized in Table 1 [4][5][6]. A benefit to using the combination of oral Midodrine and subcutaneous Octerotide is the ability to use this therapy in the outpatient setting [3].…”
Section: Discussionmentioning
confidence: 99%
“…Midodrine appears more effective when given at a dose of 15 mg 3 times daily with reversal of HRS in 88% of treated patients compared to only 33% of those receiving <12.5 mg 3 times daily. 40 However, terlipressin was superior to midodrine and octreotide in a randomized controlled trial. 41 In patients who require IV vasopressor support, use of norepinephrine is preferred in patients with cirrhosis because it has been shown to improve renal outcomes in patients with HRS.…”
Section: Renal Failurementioning
confidence: 95%
“…The study had 81 participants. The study also claimed to have a significant outcome for patients with hepatorenal syndrome but the methodology was weak for an observational trial 7 . The study selected for this appraisal showed a significant outcome with the use of octreotide, midodrine, and albumin, similar to the previous study, but had a total of 162 participants 8 .…”
Section: Literature Reviewmentioning
confidence: 99%